Chest CT Severity Score in COVID-19 at the Time of Admission and Relationship with Outcome and Duration of Admission-an Early Promising Prognostic Indicator - Parmar, Jitendra; Patel, Drashti; Patel, Tapan; Shah, Sandip; Singh, Manoj; Prasad, Shanti Bhushan (Archives of Clinical and Biomedical Research, 2022)
Purpose: The CT Severity Score has great significance in assessing the extent of pneumonia involvement with differentiation of mild, critical and severe types and helps clinicians achieve early diagnosis and accurate treatment. Material and methods: 100 COVID-19 positive patients were analyzed for CT-SS and its correlation with clinical severity, laboratory markers and duration of hospital stay. The ROC curve was analyzed to obtain the optimum CT-SS threshold to discriminate patients in the common group from the patients of severe & critical groups and discriminate patients in the critical group from the patients of severe & common groups. Results: The study comprised 57 common category, 23 severe category and 20 critical category patients. The mean chest CT-SS score was highest in critical patients (35.95), higher in severe patients (25.52) than common patients (12.18) with mean duration of admission was 13.35, 12 and 7.65 days respectively (p-value of 0.000). The optimum CT-SS threshold for discriminating patients in the common group from the patients of severe & critical groups was 21.5 with sensitivity of 93%, specificity of 86%. The optimum CT-SS threshold for discriminating patients in the critical group from the patients of severe & common groups was 28.5 with a sensitivity & specificity of 90%. Conclusion: Initial Chest CT-SS showed significant association with duration of hospital stay and short-term prognosis of patients. Chest CT Severity Score can be used to evaluate the clinical severity of the patients on initial scans, to differentiate common, severe and critical patients and decide their management.